Ex ante analysis of new bean technology in Southern Huila - Arcia, G; Sanders, J.H. (International Center for Tropical Agriculture, 1980)
The trials conducted by CIATs Bean Economics Program in southern Huila (Colombia) have indicated that in this region monoculture bean yields can be increased 1-1.5 t/ha through improved agronomic practices. This paper is an ex ante analysis of the effect of this new technology on farmers` income, taking into account factors that could potentially limit their adoption. Linear programming, with activities including both current and potential technologies, was used. Farms were divided according to size and soil fertility. A technology proposed by the CIAT (new agronomic practices and storage) for beans is analyzed as compared to the adoption of a new coffee technology, taking into account credit, prices,and the rate of return on capital. It is concluded that improved agronomic practices alone do not affect income; however, in combination with the use of storage, economic incentives to adopt the technological package are produced. This can be accomplished with more flexible credit conditions. In relation to the model used for analyses, the factor risk and probabilistic and stochastic input-output coefficients could be incorporated into the farmers` objective functions. Finally the presence of a new category of farmers able to take risks in production and marketing was detected. The identification of special characteristics of this category will be an objective of future research, that will be based on quadratic programming. (CIAT)